Nocturnal activity in wild chimpanzees (Pan troglodytes): Evidence for flexible sleeping patterns and insights into human evolution. Issue 3 (10th July 2018) - Tagg, Nikki; McCarthy, Maureen; Dieguez, Paula; Bocksberger, Gaëlle; Willie, Jacob; Mundry, Roger; Stewart, Fiona; Arandjelovic, Mimi; Widness, Jane; Landsmann, Anja; Agbor, Anthony; Angedakin, Samuel; et al.
Abstract: Objectives: We investigated occurrences and patterns of terrestrial nocturnal activity in wild chimpanzees ( Pan troglodytes ) and modelled the influence of various ecological predictors on nocturnal activity. Methods: Data were extracted from terrestrial camera‐trap footage and ecological surveys from 22 chimpanzee study sites participating in the Pan African Programme: The Cultured Chimpanzee. We described videos demonstrating nocturnal activity, and we tested the effects of the percentage of forest, abundance of predators (lions, leopards and hyenas), abundance of large mammals (buffalos and elephants), average daily temperature, rainfall, human activity, and percent illumination on the probability of nocturnal activity. Results: We found terrestrial nocturnal activity to occur at 18 of the 22 study sites, at an overall average proportion of 1.80% of total chimpanzee activity, and to occur during all hours of the night, but more frequently during twilight hours. We found a higher probability of nocturnal activity with lower levels of human activity, higher average daily temperature, and at sites with a larger percentage of forest. We found no effect of the abundance of predators and large mammals, rainfall, or moon illumination. Discussion: Chimpanzee terrestrial nocturnal activity appears widespread yet infrequent, which suggests a consolidated sleeping pattern. Nocturnal activity may be driven by the stress of high daily temperatures and may be enabled at low levels of human activity. Human activity may exert a relatively greater influence on chimpanzee nocturnal behavior than predator presence. We suggest that chimpanzee nocturnal activity is flexible, enabling them to respond to changing environmental factors.